BMI-based Prenatal Vitamins to Ameliorate Oxidative Stress in Obese Pregnant Women: A Randomized Controlled Trial (P11-135-19). (13th June 2019) - Sen, Sarbattama; Herlihy, Mary; Hacker, Michele; Mcelrath, Thomas; Cherkerzian, Sara; Oken, Emily; Meydani, Simin
Abstract: Objectives: Obesity during pregnancy is associated with inflammation and oxidative stress and concomitant depletion of nutritional antioxidant defenses, which may be implicated in adverse perinatal and long-term childhood outcomes. The objective of this study is to determine whether providing a BMI-based prenatal vitamin (BMI-PNV) to pregnant women with obesity would raise concentrations of key antioxidant vitamins (vit) and decrease markers of inflammation and oxidative stress during pregnancy. Methods: This was a double-blind, randomized controlled trial of a BMI-PNV (higher amounts of vit C (250%), E (200%), B6 (900%) and folic acid (200%)) compared to a standard prenatal vita (Std-PNV) in obese pregnant women. We recruited pregnant women with a BMI ≥ 30kg/m2 at their initial prenatal visit (< 13weeks gestation) and collected blood and urine at baseline, 24–28 weeks and 32–36 weeks to measure vit C, E, B6 and folate and markers of inflammation (C Reactive Protein, interleukin (IL)-6, 8 and 1β) and oxidative stress (8-epi-PGF2α and malonyldialehyde). We collected pregnancy and infant health data from enrollment to delivery. We used linear regression to evaluate associations between treatment arm and outcomes. Results: We enrolled 126 participants (63 in each arm) and 102 (51 per arm) completed follow-up through delivery. Mean ± SD baseline BMI was 35.7 ± 6.3 kg/m2 in the BMI-PNV and 35.5 ± 4.8kg/m2 in the STD-PNV groups. The baseline demographic characteristics are presented in Table 1. Randomization was mostly successful, but there were baseline differences between groups in biomarker levels and infection status for which we adjusted. Concentrations of vitamins B6 and C were greater in the BMI-PNV group than in the Std-PNV group at 24–28 weeks (B6 : β = 0.86nmol/L, P  < 0.0001; C: β = 0.15 umol/L, P  = 0.02) and vitamin B6 at 32–36 weeks (β = 0.66 nmol/L, P  = 0.0002) (Table 2). There were no differences in any biomarker of inflammation or oxidative stress by randomization group. There were no differences in maternal or neonatal clinical outcomes by randomization group. Conclusions: Providing higher concentrations of key antioxidant vitamins during pregnancy increased systemic concentrations of some of the antioxidant nutrients but did not decrease markers of inflammation and oxidative stress. Larger studies are needed to examine the impact on clinical outcomes. Funding Sources: NIH National Institute of Child Health and Human Development, NIH Office of Dietary Supplements, Charles H. Hood Foundation. Supporting Tables, Images and/or Graphs: